Individual participant data meta-analysis of metabolomics on sustained knee pain in primary osteoarthritis patients. (19th September 2022) - Costello, Christie A; Rockel, Jason S; Liu, Ming; Gandhi, Rajiv; Perruccio, Anthony V; Rampersaud, Y Raja; Mahomed, Nizar N; Rahman, Proton; Randell, Edward W; Furey, Andrew; Kapoor, Mohit; Zhai, Guangju
Abstract: Objectives: Knee pain is the major driver for OA patients to seek healthcare, but after pursuing both conservative and surgical pain interventions, ∼20% of patients continue to report long-term pain following total knee arthroplasty (TKA). This study aimed to identify a metabolomic signature for sustained knee pain after TKA to elucidate possible underlying mechanisms. Methods: Two independent cohorts from St John's, NL, Canada ( n = 430), and Toronto, ON, Canada ( n = 495) were included in the study. Sustained knee pain was assessed using the WOMAC pain subscale (five questions) at least 1 year after TKA for primary OA. Those reporting any pain on all five questions were considered to have sustained knee pain. Metabolomic profiling was performed on fasted pre-operative plasma samples using the Biocrates Absolute IDQ p180 kit. Associations between metabolites and pair-wise metabolite ratios with sustained knee pain in each individual cohort were assessed using logistic regression with adjustment for age, sex and BMI. Random-effects meta-analysis using inverse variance as weights was performed on summary statistics from both cohorts. Results: One metabolite, phosphatidylcholine (PC) diacyl (aa) C28:1 (odds ratio = 0.66, P = 0.00026), and three metabolite ratios, PC aa C32:0 to PC aa C28:1, PC aa C28:1 to PC aa C32:0, and tetradecadienylcarnitine (C14:2) to sphingomyelin C20:2 (odds ratios = 1.59, 0.60 and 1.59, respectively; all P < 2 × 10 −5 ), were significantly associated with sustained knee pain. Conclusions: Though further investigations are needed, our results provide potential predictive biomarkers and drug targets that could serve as a marker for poor response and be modified pre-operatively to improve knee pain and surgical response to TKA.